Investigation of Solid Waste Collection and Source Separation Alternatives in Besiktas District with Zero Waste Focus and GIS Supported - Apaydin, Omer; Han, Gul Sumeyra Akcay (Mehmet Sinan Bilgili, 2020)
Solid waste management presents a situation that needs to be performed with the logic from cradle to cradle. Within the scope of international conventions, it is known that a vision has been determined for the variety of waste management options. This is perceived as an important and useful vision with a focus on resource conservation. In this context; it contains restrictions in terms of the amount of organic waste in the process of disposal and landfill, which is the last step of the waste hierarchy. As a result; it is essential that the reduction-oriented recycling alternatives are intensely implemented in solid waste management processes. It is a known fact that recycling options in waste disposal processes can be achieved only in accordance with technological realities and with the aim of obtaining high product quality by separating them at the source. In this context, it is important to separate organic wastes and material recyclable wastes at the source and integrate them into disposal processes by collecting them separately. In this study; entered into force in Turkey in 2019, to comply with the Zero Waste Regulations, focused on source separation studies were analyzed in the Besiktas district. By using Arc Map, digital road maps produced by Besiktas Municipality, thematic layers containing attribute data such as existing solid waste collection container points / numbers and solid waste loads in each street and avenue were created and analyzes were made based on Geographical Information System. The effects of new routes, which are alternative to the selected solid waste collection routes, on the collection costs were analyzed using the Network Analysis program running on the Arc Map platform. According to the results obtained; it is concluded that the separation and separate collection operations in the current source are higher than the collection process costs made by using alternative routes created within the scope of this study.
Keywords: Besiktas; Source separation; waste hierarchy; zero waste; Geographic Information Systems (GIS); Route optimization; Arc Map; Network Analysis; Engineering; Environmental Sciences & Ecology